Parental Oral Health Literacy and Its Associated Impact On Child’s Oral Health Profile Among 15-Years-Old School Children in the Population of Multan, South Punjab, Pakistan (Medical Forum Monthly, 2023)
Objective: The purpose of the study was to determine the parental oral health literacy and its associated impact on child’s oral health profile among 15-years-old school children.Study Design: A cross-sectional study.Place and Duration of Study: This study was conducted at the Tertiary Care Dental Hospital of Multan, South Punjab, Pakistan from 05- July 05-2022 till December 2022.Materials and Methods: The sample size was 346 calculated by using WHO sample size calculator. The data was collected through a well-structured questionnaire from the children and their parent’s by using convenient sampling technique. All the data was analyzed by using IBM SPSS version 24.Results: The results of the present study showed that the educational level of the parents was 54% education below intermediate and 46% above intermediate level. Moreover, only 21.6% of the respondent children agreed that they had pain in their teeth, 19 % of the children had bad breath and 44.5% of them had spaces between their teeth. Additionally, 75% of them were satisfied with their overall oral health. 64.4% of the parents said that were not able to pay attention to their oral health and 58.3% of them were not able to manage time for themselves in order to carry out activities necessary to maintain a good oral hygiene and oral health.Conclusion: The current study has concluded that higher parental educational level has got a direct relationship with their children’s good oral health. Moreover, children can face many problems while chewing food such as pain in their teeth, particularly when they have associated oral health concerns prevailing side by side.